Effect of carbofuran on some biochemical indices of human erythrocytes in vitro - Sharma, R. K.; Jaiswal, S. K.; Siddiqi, N. J.; Sharma, B. (Cellular and Molecular Biology, 2012)
Pesticides are used in agriculture to protect crops. Its widespread use in agriculture represents a threat not only to the environment but also to human populations exposed to them. Erythrocytes serve as an excellent model system to study the interaction of pro-oxidants. Organocarbamates are known to produce free radical species and to induce toxicity to different body systems resulting into hematological and biochemical perturbations. The information available relating to the effect of organocarbamates on the biochemical indices of human erythrocytes is scanty. Therefore, the present study was carried out to evaluate the impact of carbofuran, a carbamate pesticide, on some key biochemical indices of human erythrocytes’ membrane. The oxidative potential of the pesticide was assessed in vitro by monitoring the levels of malondialdehyde (MDA) and reduced glutathione (GSH) in human erythrocytes exposed to different sub-acute concentrations (0, 2.5, 5, 10, 25 and 50µM) of carbofuran for different time intervals; maximally up to 120 min. It was observed that the level of MDA was elevated and that of GSH was significantly decreased after treatment of erythrocytes with carbofuran. The results indicated the negative impact of carbofuran in concentration and time dependent manner. Carbofuran was also found to sharply inhibit the activity of membrane bound Na+K+-ATPase at higher carbofuran concentrations (10, 25 and 50µM). Further, carbofuran at aforesaid concentrations was also found to cause significant rise in the osmotic fragility of human erythrocytes indicating adverse effect on membrane fluidity. The results of present study suggested that carbofuran was able to alter the oxidative balance and the stability of human erythrocytes membrane.